Hauora Māori - Māori health: a right to equal outcomes in primary care - Nicolette Sheridan; Rawiri McKree Jansen; Matire Harwood; Tom Love; Timothy Kenealy; The Primary Care Models Study Group (BMC, 2024)
Abstract Background For more than a century, Māori have experienced poorer health than non-Māori. In 2019 an independent Tribunal found the Government had breached Te Tiriti o Waitangi by "failing to design and administer the current primary health care system to actively address persistent Māori health inequities". Many Māori (44%) have unmet needs for primary care. Seven models of primary care were identified by the funders and the research team, including Māori-owned practices. We hypothesised patient health outcomes for Māori would differ between models of care. Methods Cross-sectional primary care data were analysed at 30 September 2018. National datasets were linked to general practices at patient level, to measure associations between practice characteristics and patient health outcomes. Primary outcomes: polypharmacy (≥ 55 years), HbA1c testing, child immunisations, ambulatory sensitive hospitalisations (0-14, 45-64 years) and emergency department attendances. Regressions include only Māori patients, across all models of care. Results A total of 660,752 Māori patients were enrolled in 924 practices with 124,854 in 65 Māori-owned practices. Māori practices had: no significant association with HbA1c testing, ambulatory sensitive hospitalisations or ED attendances, and a significant association with lower polypharmacy (3.7% points) and lower childhood immunisations (13.4% points). Māori practices had higher rates of cervical smear and cardiovascular risk assessment, lower rates of HbA1c tests, and more nurse (46%) and doctor (8%) time (FTE) with patients. The average Māori practice had 52% Māori patients compared to 12% across all practices. Māori practices enrolled a higher percentage of children and young people, five times more patients in high deprivation areas, and patients with more multimorbidity. More Māori patients lived rurally (21.5% vs 15%), with a greater distance to the nearest ED. Māori patients were more likely to be dispensed antibiotics or tramadol. Conclusions Māori practices are an expression of autonomy in the face of enduring health system failure. Apart from lower immunisation rates, health outcomes were not different from other models of care, despite patients having higher health risk profiles. Across all models, primary care need was unmet for many Māori, despite increased clinical input. Funding must support under-resourced Māori practices and ensure accountability for the health outcomes of Māori patients in all models of general practice.